PENGARUH MEDIA CANVA BERBANTU QR CODE TERHADAP HASIL BELAJAR IPS - Ainnur Ristyanti; Diyas Age Larasati; Diah Yovita Suryarini (Sekolah Tinggi Pariwisata Mataram, 2022)
Teachers' teaching of social science learning is not supported by the use of learning media and is monotonous, causing students to appear bored after the lesson. This has an effect on the low student learning outcomes. It is hoped that by using Canva media combined with a QR code, students will be more interested in learning and will find it easier to understand the subject matter. The purpose of this study is to see how QR code-assisted Canva media affected social science learning outcomes for class IV students at SD Negeri 220 Gresik. This study is a Nonequivalent Control Group Design experimental study. The sample size was 60 students, who were divided into two classes: IV A (30 students as the experimental class) and IV C (30 students as the control class). This study's instruments were observation sheets and tests. According to the findings of the study, (1) Data analysis results show that the average value of student learning outcomes in the experimental class is 99 and 78.3 in the control class. (2) The results of hypothesis testing using the t-test show the sig value of the output pair 1 and pair 2. (2 tailed) of 0.000<0.05, thus H1 is accepted and H0 is rejected, indicating that Canva media with the help of QR Code has a significant effect on elementary school social science learning outcomes.